Konsep pengembangan kurikulum PAI berbasis kompetensi perspektif Muhaimin di perguruan tinggi agama Islam - Abrori, M. Sayyidul; Khodijah, Khodijah; Setiawan, Dedi (Kuras Institute, 2023)
This paper is focused on describing the concept of developing a competency-based PAI curriculum from the Muhaimin perspective in Islamic Higher Education. The discussion of this competency theory cannot be separated from several problem factors that still often arise in solving problems faced by students after they finish their college studies. Therefore, Muhaimin offered a solution to solve existing problems by initiating the concept of developing a competency-based PAI curriculum to overcome these problems. This study includes a literature study design with a philosophical approach. Documentation of primary and secondary sources is the method of this research. The results of this study indicate that; first, the steps for developing a competency-based curriculum are determining educational goals, identifying and selecting learning experiences, organizing curriculum materials and learning activities, and evaluating the results of curriculum implementation. Second, the identification of competency-based PAI curriculum development in the curriculum development method has been seen from the general objectives, classification of objectives, and specific objectives. Third, the urgency of developing a competency-based curriculum is one solution for every educational actor, especially lecturers who are required to be able to develop a curriculum in carrying out learning activities on campus in order to prepare graduates who are competent in their fields.